SEPERENSI (SENAM, PENYULUHAN, PEMERIKSAAN TENSI) SEBAGAI UPAYA PENANGANAN HIPERTENSI DI KELURAHAN SONDAKAN SURAKARTA - Ifalahma, Darah; Yuliana, Ana; Sulistiyanti, Anik; Asri, Novia Kartika Hayu; Safitri, Herni (LPPM Universitas Bina Bangsa, 2025)
Hypertension is a condition or state of a person's blood pressure exceeding the normal threshold, which is >140 mmHg for systolic and >90 mmHg for diastolic. Hypertension is also often referred to as heart and blood vessel disease. If hypertension continues in the long term, it can trigger diseases such as stroke, heart attack, heart failure and the main cause of chronic kidney failure. Risk factors for hypertension are age, genetic factors, gender, environmental factors, smoking, being overweight (obesity), stress, lack of exercise, consuming fatty foods and consuming foods high in salt. From the results of filling out the Target Assistance Card Registration Form at the Integrated Health Post in the Pajang Health Center area in RW 11 Sondakan Laweyan Surakarta, the most common problem in the community was hypertension. To overcome the problem of hypertension in RW 11, an activity was carried out, namely SEPERENSI (Exercise, Counseling and Blood Pressure Examination). The purpose of this activity is to increase knowledge about Hypertension Management through SEPERENSI activities. The method of implementing the activity was carried out by providing education in the form of health education on handling hypertension with a hypertension diet and acupressure to 60 respondents of Sondakan Village residents. Community participation was also increased for gymnastics (active movement) and blood pressure checks. The results of this activity were that there was an increase in respondent knowledge between before and after counseling was given. The increase in knowledge score was 32%. At the end of the activity, respondents understood the handling of hypertension and were willing to apply the results of the activity independently.